Multifaceted role of galanin in brain excitability - Nicolas N Rieser; Milena Ronchetti; Adriana Lea Lea Hotz; Stephan CF Neuhauss (eLife, 2025)
Galanin is a neuropeptide, which is critically involved in homeostatic processes like controlling arousal, sleep, and regulation of stress. This extensive range of functions aligns with implications of galanin in diverse pathologies, including anxiety disorders, depression, and epilepsy. Here, we investigated the regulatory function of galanin on whole-brain activity in larval zebrafish using wide-field Ca2+ imaging. Combining this with genetic perturbations of galanin signaling and pharmacologically increasing neuronal activity, we are able to probe actions of galanin across the entire brain. Our findings demonstrate that under unperturbed conditions and during epileptic seizures, galanin exerts a sedative influence on the brain, primarily through the galanin receptor 1 a (galr1a). However, exposure to acute stressors like pentylenetetrazole (PTZ) compromises galanin’s sedative effects, leading to overactivation of the brain and increased seizure occurrence. Interestingly, galanin’s impact on seizures appears to be bidirectional, as it can both decrease seizure severity and increase seizure occurrence, potentially through different galanin receptor subtypes. This nuanced interplay between galanin and various physiological processes underscores its significance in modulating stress-related pathways and suggests its potential implications for neurological disorders such as epilepsy. Taken together, our data sheds light on a multifaceted role of galanin, where galanin regulates whole-brain activity but also shapes acute responses to stress.